Effect of Bainitic Isothermal Treatment on the Microstructure and Mechanical Properties of a CMnSiAl TRIP Steel - Alexis Guzmán; Alberto Monsalve (Metals, 2022)
TRIP-assisted CMnSiAl steels with a fully martensitic initial microstructure have been studied in order to investigate the effect of partial substitution of Si by Al. The steel was fabricated by casting in a sand mold, hot forged, homogenizing, hot rolling, cold rolling, intercritical annealing, and finally, an isothermal bainitic treatment. During the intercritical annealing at 1023 K (750 °C) for 420 s, a matrix with a microstructure consisting of 50% proeutectoid ferrite was induced and after isothermal treatment at 663 K (390 °C) for 300 s, a microstructure of ferrite, bainite, and retained austenite was obtained. This austenite was carbon enriched and therefore stabilized, with an Ms lower than original austenite, before bainitic treatment. Microstructure and tensile properties have been analyzed, comparing these results with those corresponding to a commercial TRIP 780 steel. During tensile tests, retained austenite changes from 8.1 to 1.9%vol, with a total elongation of 23.2%, which demonstrates the TRIP effect. Texture analysis showed a weak γ-fiber in the steel, which deteriorates the drawing properties of the steel. The maximum elongation during the tensile test of this steel was obtained at 323 K (50 °C), correlating with the TRIP effect present in steel, which is favored when working within the critical zone of temperatures <semantics><msubsup>Msσ</msubsup></semantics> and <semantics>Md</semantics>. The results show that partial substitution of Si by Al decreases yield stress, ultimate tensile strength, increases the total elongation, and decreases the temperature for maximum elongation, related to TRIP 780.